Post-operative endophthalmitis after immediate sequential bilateral cataract Surgery: a retrospective study from Pakistan. - Siddiqui , Muhammad Abdul Rehman; Hussain , Syed Zohaib Maroof; Irfan Jeeva (Journal of the Pakistan Medical Association, 2021)
Objective: The aim of this study was to assess the frequency of post-operative complications after immediate sequential bilateral cataract surgery (ISBSC) in Pakistan, a low-middle income country. Methods: This is a 10-year retrospective study including all consecutive patients who underwent ISBCS between 1st January 2009 and 31st December 2018 at Aga Khan University Hospital (AKUH), Karachi, Pakistan. We identified potential patients through the procedure coding system of the hospital. A structured proforma was used to collect information. The inclusion criterion was bilateral cataract extraction without any additional secondary procedures. Patients who underwent a planned additional procedure on the operated eye on the same day, such as phaco combined with vitrectomy, corneal graft, or glaucoma surgery, were excluded. The primary outcome measure was the incidence of endophthalmitis. The data were analyzed with Statistical Package for the Social Sciences (SPSS) version 23.0, IBM Corporation, Armonk, New York, United States. A p-value of < 0.05 was considered significant. Results: We identified 352 patients through the coding system of our hospital who underwent ISBCS from January 2009 to December 2018. A total of 298 patients (596 eyes) met the inclusion criteria. The mean age was 33.14±25.83 years. Participants were divided into two age groups: <16 (39.26 %) years and >16 (60.73) years of age. Best-corrected visual acuity improved from -0.5650±8.2027 to -0.0043+4.05. Among 596 eyes, we found no case of post-operative endophthalmitis after ISBCS. Conclusions: ISBCS is a safe procedure in selected patients undergoing cataract surgery in a low-middle income country. Continuous...